Surgical Anatomy of the Upper Face and Forehead - Garritano, Frank Gerard; Quatela, Vito C. (Facial Plastic Surgery, 2018)
Aesthetic ideals regarding proportion and balance of the face have existed for centuries. The upper third of the face, including the brow, forehead, and temple, provides an important contribution to the overall facial aesthetic. This is especially true given how the brow frames the eyes, and the eyes serve as the key focal point in our interactions with others. There exists a variety of surgical and nonsurgical procedures aimed at improving the aesthetic of the upper portion of the face, and a thorough knowledge of the surgical anatomy of the upper face and forehead is critical to their successful execution.
Keywords: upper face; forehead; brow; anatomy